2008
DOI: 10.1021/ja802511d
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy Studies of NaLaMgWO6: Spontaneous Formation of Compositionally Modulated Stripes

Abstract: Transmission electron microscopy studies of the perovskite NaLaMgWO 6 reveal the formation of a complex, compositionally modulated structure. Annular dark field scanning transmission electron microscopy images and scanning transmission electron microscopy-electron energy-loss spectroscopy scans show that this modulation involves a repeating pattern of La-rich and La-poor stripes, each stripe 6 a p or approximately 24 A wide (where a p is the edge length of the simple cubic perovskite unit cell). High-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
64
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 31 publications
(45 reference statements)
6
64
0
Order By: Relevance
“…Following that report similar modulations were reported in a family of B 3 þ (Al, Mn, Cr) substituted Li systems and, more recently, in three different Li-free alkali-containing perovskites based on Na þ and K þ [2,[4][5][6][7]. While chemically similar, the modulations observed for each system are unique in at least the magnitude of the periodic repeat.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Following that report similar modulations were reported in a family of B 3 þ (Al, Mn, Cr) substituted Li systems and, more recently, in three different Li-free alkali-containing perovskites based on Na þ and K þ [2,[4][5][6][7]. While chemically similar, the modulations observed for each system are unique in at least the magnitude of the periodic repeat.…”
Section: Introductionsupporting
confidence: 65%
“…Recent studies have revealed that several (AA 0 )BO 6 ordered, alkali-based mixed A-site perovskites exhibit unusual nanoscale modulations in composition and structure [1][2][3][4][5][6][7]. The first observation of A-site driven modulations was made on compositions in the lithium-based (Nd 2/3 À x Li 3x )TiO 3 solid solution system [1].…”
Section: Introductionmentioning
confidence: 99%
“…They also share several similarities to the striped patterns observed in ͑NaLa͒͑MgW͒O 6 which were argued to result from an ordered phase separation of Na-rich, ͑NaLa͒͑MgW͒O 6 , and Na-deficient, La 4/3 ͑MgW͒O 6 , end member phases. 5 The nanoscale structures in both of those systems also involve a periodic twinning of the a − a − c 0 ͑Glazer notation͒ octahedral tilt system, the same tilt system reported for ͑NaNd͒͑MgW͒O 6 . 8,9 With these similarities it is tempting to conclude the modulations reported here for ͑NaNd͒͑MgW͒O 6 involve periodic phase separation into ͑NaNd͒͑MgW͒O 6 domains separated by Na-deficient regions of Nd 4/3 ͑MgW͒O 6 .…”
mentioning
confidence: 55%
“…For ͑NaLa͒͑MgW͒O 6 the modulation occurs in one dimension leading to a striped pattern of light and dark regions with a repeat distance of 12a p ; compositional analyses indicated separation into Narich ͓͑NaLa͒͑MgW͒O 6 ͔ and Na-deficient ͓La 4/3 ͑MgW͒O 6 ͔ phases. 5 HRTEM images of ͑KLa͒͑MnW͒O 6 provided evidence for checkerboard type modulations in another A + / A 3+ mixed A-site system. 6 This paper focuses on the perovskite ͑NaNd͒͑MgW͒O 6 , one of several ͑AЈAЉ͒͑BЈBЉ͒O 6 perovskites with both A-and B-site ordering.…”
mentioning
confidence: 91%
“…[4][5][6] We used this approach to improve on previous eutectoid 7 and other [8][9][10][11] syntheses of CFO/BTO composites. Avellaneda and Harshe 12 already demonstrated that solidification of eutectic BTO-CFO leads to lamellar microstructures.…”
mentioning
confidence: 99%